Building an Image Through Proper Planning: The Key to Public Relations Success - Angel Avrielya Charlyandra; Kamilina Indhaka Tholibin; Seprinda Elin Anggita Rahayu; Khusnul Khotimah (Yayasan Adra Karima Hubbi, 2024)
Background. In the organization, every planning is carefully calculated, be it the state, companies, or educational institutions. Planning is also determined in an educational institution. Educational institutions also have an initial reference to build and step into the institution of their dreams. Each department and division already has several planning programs, be it the curriculum, infrastructure, student affairs and others, including public relations. Purpose. This study aims to explain and analyze how planning and imagery as public relations suggestions Method. The method carried out in writing this article is a literature research method using data collection techniques. Results. The results of the study show that planning and image as the target of public relations are important in the institution. Conclusion. The model in public relations planning is a set of knowledge that needs to be known, such as what, how, and how much the institution is able to reach the desired institution. The model here in question is the steps that will be taken by an institution to realize its plan.